Antimicrobial activity of United Arab Emirates indigenous medicinal plants Prosopis cineraria, Prosopis juliflora and Acacia tortilis - Duaa Salem Alkaabi (Hamdan Medical Journal, 2020)
Background: Prosopis cineraria, Prosopis juliflora and Acacia tortilis are widely distributed plants in the United Arab Emirates (UAE). They have beneficial uses in the traditional medicine and animal fodder. The exploration of these plants is of potential value to UAE economy through their large-scale utilisation. The leaves of these plants were collected to study their main antimicrobial constituents. This study highlights the potential utilisation of these plants leaves as antimicrobial agents. Aims: The aim of this study is to explore the antimicrobial activity of the above three plants. Subjects and Methods: Dried leaves of above plants were extracted with aqueous ethanol. Extracts subjected to phytochemical screening and thin-layer chromatographic (TLC) separation to determine the compounds present. Antimicrobial activity tests were performed for the extracts and fractions obtained by preparative TLC. Results: Tannins constitute the major compounds in all three plant extracts. A TLC solvents system was developed for the separation of the phytochemical constituents in the three aqueous plant extracts. P. juliflora aqueous extract presented the highest activity against all tested microorganisms at a concentration of 5 mg dry leaf material/disc; inhibition zones exhibited by P. juliflora were as follows: ZoI (23 mm) against Escherichia coli, ZoI (18 mm) against Staphylococcus aureus and ZoI (12 mm) against Candida albicans. Isolated fraction 1 from P. juliflora aqueous extract, containing two major spots, exhibited intermediate activity followed by fraction 3, fraction 2 had no activity. Conclusions: P. juliflora leaves revealed the significant antimicrobial activity. It is potential for the treatments of infectious diseases. The developed TLC solvent system may further be applied on column chromatographic separation of pure active compounds from P. juliflora.